Dinamika dan Realitas Keadilan dalam Perspektif Islam - Azhar, Purjatian (Islam & Contemporary Issues, 2022)
The highest form of goodness or virtue is justice. Islam places a high priority on justice. Since the dawn of thought in humans, justice has been perceived as the primary issue. Because justice in law is frequently defined in terms of interests, the formulation of justice in law is extremely important. In contrast, according to Islamic law, justice is always connected to the divine, specifically in the context of human relationships with God and other people. A viewpoint that connects justice and truth is shown by the way Islamic reasoning about law and justice is constructed. Islam's approach to justice differs from that of the Sunni, Shia, and Khawarij groupings in terms of its dynamics. According to the Sunni perspective, the caliphate is essential for the community's survival as well as for putting the law into practice. The Shia believe that an infallible imam encompasses both inner and outside spiritual and physical leadership in addition to being a leader in Islamic law. The Khawarij, on the other hand, are supporters of a school of thought that, at the start of the Islamic era, was at odds with both Sunni and Shi'a ideologies.